How control-friendly is a computing system? And how control-friendly could it be?. Issue 2 (2020) - Leva, Alberto; Seva, Silvano; Terraneo, Federico; Papadopoulos, Alessandro Vittorio; Maggio, Martina
Abstract: To date, not that much. Improvements are possible, but some system-theoretically grounded re-design is necessary. We discuss the matter based on our experience, and as a consequence, we come to distilling some design clues and research directions.